2017
DOI: 10.1111/papt.12158
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia according to Bucci's multiple code theory: A preliminary investigation with healthy and hypertensive individuals

Abstract: A relation between alexithymia and RA has been proposed on theoretical grounds, but there has been minimal empirical investigation. This was the first study to employ both a self-report measure and a structured interview for measuring alexithymia in relation to RA. The results of this study suggest a complex, nonlinear relation between alexithymia and RA; this finding is essentially obtained with the structured interview measure of alexithymia. This relation is presumably influenced by subject-specific charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…The Italian Sensory Somatic Dictionary (ISensD) is a list of Italian words related to the body and bodily activities, and to sensory processes and/or descriptions of symptoms (Di Trani, Mariani, Renzi, Greenman, & Solano, 2018 ). The number of ISensD words in the speech sample is a measure of the arousal of bodily subsymbolic aspects of emotion schemas.…”
Section: Methodsmentioning
confidence: 99%
“…The Italian Sensory Somatic Dictionary (ISensD) is a list of Italian words related to the body and bodily activities, and to sensory processes and/or descriptions of symptoms (Di Trani, Mariani, Renzi, Greenman, & Solano, 2018 ). The number of ISensD words in the speech sample is a measure of the arousal of bodily subsymbolic aspects of emotion schemas.…”
Section: Methodsmentioning
confidence: 99%
“…In the MCT, it is hypothesized that trauma or conflicts can disturb an appropriate development of the three systems, which is also disruptive to the RP’s functioning. This kind of disconnection can be applied to both somatic and mental pathology [ 22 , 23 , 24 ], and it could be increased if there are aversive experiences for negative events and emotions, since some distancing processes are activated [ 25 ]. The greater the disconnection is, the more a person feels emotional arousal without being able to communicate their experience with words.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted that alexithymia is associated with deficits in labelling emotional facial expressions, with reduced perceptual abilities, with impaired semantic representations of emotional concepts and with neither specific emotional facial expressions nor a specific valence (Grynberg et al, 2012;Pedrosa Gil et al, 2009;Ridout, Thom, & Wallis, 2010). Moreover, a recent study by Di Trani, Mariani, Renzi, Greenman and Solano (2018) has revealed a relationship between alexithymia levels and several indexes related to RP in the general population. By contrast, no studies have explored the connections between RP and alexithymia in clinical process, such as expression writing technique, in order to examine several implications of alexithymia for clinical treatments.…”
Section: Introduction Expressive Writing Interventions and The Alexithymia Constructmentioning
confidence: 99%